Evaluation of stromal proteins expression – tenastin and fibronectin – in the cysts and dental derived neoplasms of the facial part of the cranium - Grodecka, Joanna; Kobos, Józef; Zielińska-Kaźmierska, Bogna; Manowska, Bogusława (Contemporary Oncology/Współczesna Onkologia, 2009)
Introduction: The most frequent tumors of the facial part of the cranium are neoplasms and dental derived cysts. Still, the mechanisms of dental derived origin is unknown. Particularly it is ambiguous what the factors, that leads to neoplasms transformation of the epithelial factor and mesenchymal tooth bud, are. The latest researches indicate that stromal proteins, inter alia – tenastin and fibronectin could have a great influence on local progression of neoplasms. Aim of the study: Evaluation of the tenastin and fibronectin expression in the cysts and dental derived neoplasms of the facial part of the cranium. Material and methods: 74 patients hospitalized in Department Cranio-Maxillofacial and Oncology Surgery of Medical University of Lodz between 1982-2002 were analyzed. Patients were divided into 3 groups in relation to histopatology results: • I group – odontogenic cysts – 42 persons, • II group – adamantinomas – 18 persons, • III group – odontogenic neoplasms excluded adamantinomas – 14 persons. Conclusions: 1. Tenastin and fibronectin was correlated with inflammation process in the patients with dental derived cysts. 2. Highly intense tenastin expression was correlated with recurrence of the neoplasms in the patients with dental derived neoplasms. 3. Fibronectin expression was correlation with good behavior of neoplasms (no recurrence of neoplasms).